Quality management practices among headmasters in Sri Aman rural schools / Ului Anyi - Anyi, Ului (2012)
The purpose of this study is to examine the effects of Quality Management Practices among headmasters in rural schools Sri Aman District of Sarawak. The objectives of this study is to describe management practices and style of quality management practiced by the headmaster involved and effects from quality management.Research samples comprised 36 headmasters from rural primary schools in Sri Aman District of Sarawak. These samples were chosen using random sampling method.Instrument used were questionnaires which has been self-constructed and modified from "Leadership Styles Questionnaires Flexible Training Partners. Com." A pilot test was conducted on questionnaires which shows high reliability indexes. This study was quantitative in nature. The data was analyzed using Statistical Package of Social Science (SPSS) version 16.0 for Windows to identify the mean (M) and standard deviation (SD) and interpreted descriptively. The findings showed that modem trends of management has a high level of mean score 4.53., Styles on Quality Management has a mean score of 4.43, and Effects of Quality Management practices has the highest level of mean score of 4.59. Based on the result of the study, quality management practice among headmasters shows effects on school's academic achievements or performances. The findings of this study also revealed implications the importance of using Information Communication Technology (ICT) used in school administrations or management in line with the nation's educational transformation agenda towards Vision 2020.